A systematic exploration of the effects of flexibility and basicity on sigma (σ) receptor binding in a series of substituted diamines. Issue 39 (19th September 2016) - Conroy, Trent; Manohar, Madhura; Gong, Yu; Wilkinson, Shane M.; Webster, Michael; Lieberman, Brian P.; Banister, Samuel D.; Reekie, Tristan A.; Mach, Robert H.; Rendina, Louis M.; Kassiou, Michael
Abstract : Investigating amide and open chain piperazine analogues to target the sigma 1 receptor to fight neurological disorders. Abstract : The sigma-1 receptor (S1R) has attracted a great deal of attention as a prospective drug target due to its involvement in numerous neurological disorders and, more recently, for its therapeutic potential in neuropathic pain. As there was no crystal structure of this membrane-bound protein reported until 2016, ligand generation was driven by pharmacophore refinements to the general model suggested by Glennon and co-workers. The generalised S1R pharmacophore comprises a central region where a basic amino group is preferred, flanked by two hydrophobic groups. Guided by this pharmacophore, S1R ligands containing piperazines, piperazinones, and ethylenediamines have been developed. In the current work, we systematically deconstructed the piperazine core of a prototypic piperazine S1R ligand ( vide infra ) developed in our laboratories. Although we did not improve the affinity at the S1R compared to the lead, we identified several features important for affinity and selectivity. These included at least one basic nitrogen atom, conformational flexibility and, for S1R, a secondary or tertiary amine group proximal to the anisole. Furthermore, S2R selectivity can be tailored with functional group modifications of the N-atom proximal to the anisole.